Answer:
The answer is 8
Explanation:
Simplifying
2x + 12 = 4x + -4
Reorder the terms:
12 + 2x = 4x + -4
Reorder the terms:
12 + 2x = -4 + 4x
Solving
12 + 2x = -4 + 4x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-4x' to each side of the equation.
12 + 2x + -4x = -4 + 4x + -4x
Combine like terms: 2x + -4x = -2x
12 + -2x = -4 + 4x + -4x
Combine like terms: 4x + -4x = 0
12 + -2x = -4 + 0
12 + -2x = -4
Add '-12' to each side of the equation.
12 + -12 + -2x = -4 + -12
Combine like terms: 12 + -12 = 0
0 + -2x = -4 + -12
-2x = -4 + -12
Combine like terms: -4 + -12 = -16
-2x = -16
Divide each side by '-2'.
x = 8
Simplifying
x = 8